Geography of Architectural Knowledge: Transmission, Exchange and Translation in the Eastern Adriatic - Gudelj, Jasenka (2014)
Sažetak:
The study of transmission of architectural knowledge codified in Early Modern treatises traditionally delineates a trajectory originating in Italy and moving westwards, often in the form of translated editions, exercising decisive influence on built architecture in France, Spain, Low Countries, Britain or Poland (Guillaume ed. 1988, Hart&Hicks eds. 1998, Heck, Lemerle, Pauwels eds. 2002) and. The aim of the project is to challenge this notion by introducing eastern Adriatic and Balkan region into the equation, as I shall explore the circulation of knowledge on the area within the European theoretical discourse and I also shall map the reception of texts on the art of building within the area. Influential authors such as Alberti, Serlio, Vasari, Palladio or Scamozzi informed their readers about the area in question as an important reserve of specific building materials (pietra d’Istria, wood) as well as antiquities of Pula (Gudelj 2008, Gudelj 2011). The analysis of these and other references shall include the notion of geographical and political position, the sources and the context, while a special attention shall be given to the intertextual migration of these notions between the treatises as they signal the impoverishment or an enrichment of the general knowledge on the case in question. Furthermore, a specific body of texts which reveal a glimpse of theoretical interest in architecture and urban design by authors who divided their time between the two Adriatic coasts is also to be taken into consideration, such as Benedetto Cotrugli’s Della mercatura et del mercante perfetto, written in 1458 (Grujić 1995, Grujić 2006) ; Francesco Patrizi da Cherso’s La città felice (Venice, 1553) and Niccolo di Vito Gozze's Governo della famiglia (Venice, 1589), as well as a short text about the town and fortifications of Pula, published in 1630 by a French military engineer Antoine Deville (Žmegač, 2009). The movement of the architectural knowledge depended on the different webs also to be investigated, as a number of churchmen who held offices in Catholic part of the region also played important roles in the development of theoretical reflections on architecture (Biagio Molin in Pula and Zadar, Claudio Tolomei in Korčula) while secular officers include Luca Pacioli was teaching in Zadar in 1481, where he wrote a now lost algebra manual. Moreover, the circulation of architectural treatises in the abovementioned area is to be investigated, in order to shed more light on cultural exchange through the web of mercantile routes across and along the Adriatic Rim and further inland. Books on architecture by crossing the Adriatic crossed frontiers and spheres of visual, linguistic and political influence, their messages understood without need for translation from Latin and Italian but interpreted through different, “liminal” lens. Copies of treatises still preserved in local libraries and archival document mentioning their presence in houses of nobility and architects are analyzed, as well as the explicit borrowings from treatises in the Early Modern architecture of the area, reflecting not only on the context of specific cases, but primarily on the media and the web of transmission of the architectural know-how.
HRV